Test of Mediating Effect of Employees’ Commitment between the Link of Employees’ Empowerment and Employees’ Turnover Intentions: A Study of Private Higher Educational Institutions - NIDA KHALID; DR. SAJJAD AHMAD AFRIDI; DR. MAQSOOD HAIDER; DR. SAIMA BATOOL (Journal of Business & Tourism, 2021)
The present study aimed to investigate the impact of employees’ empowerment on employees’ turnover intentions with mediating role of employees’ commitment in private higher education context. Data were collected from the faculty of the private higher educational institute via stratified random sampling. The collected data were verified through confirmatory factor analysis in AMOS. After confirming the validity the assumptions were tested via path analysis. Result revealed a negative significant effect of employees’ empowerment on employees’ intentions to quit. Moreover, the mediating effect of employees’ commitment was examined and found that fully mediates the association of employees’ empowerment and employees’ turnover intentions. The present study would be useful to the management and administration of the higher education to consider employees’ empowerment while retaining skill full employees and gain competitive advantage.